Determining the Net Present Value of Timber Investments and Comparing Investments of Different Rotations - Andres Susaeta; Chris Demers (EDIS)
Would a forest landowner be economically better off growing a forest for pulpwood production with a short rotation instead of growing the same forest for sawtimber production with a longer rotation? To help answer this and related questions, this 4-page fact sheet written by Andres Susaeta and Chris Demers and published by the UF/IFAS School of Forest Resources and Conservation presents two approaches to determine the profitability of a forest stand. The net present value (NPV) of a single rotation provides the criterion to choose between different forest project investments of equal lives, whereas the equivalent annuity approach (EAA) is employed when forest project investments have different time lengths. http://edis.ifas.ufl.edu/fr421